An overview on recent in vivo biological application of cerium oxide nanoparticles - Baskaran Stephen Inbaraj; Bing-Huei Chen (Elsevier, 2020)
Cerium oxide nanoparticles (CNPs) possess a great potential as therapeutic agents due to their ability to self-regenerate by reversibly switching between two valences +3 and +4. This article reviews recent articles dealing with in vivo studies of CNPs towards Alzheimer's disease, obesity, liver inflammation, cancer, sepsis, amyotrophic lateral sclerosis, acute kidney injury, radiation-induced tissue damage, hepatic ischemia reperfusion injury, retinal diseases and constipation. In vivo anti-cancer studies revealed the effectiveness of CNPs to reduce tumor growth and angiogenesis in melanoma, ovarian, breast and retinoblastoma cancer cell-induced mice, with their conjugation with folic acid, doxorubicin, CPM, or CXC receptor-4 antagonist ligand eliciting higher efficiency. After conjugation with triphenylphosphonium or magnetite nanoparticles, CNPs were shown to combat Alzheimer's disease by reducing amyloid-β, glial fibrillary acidic protein, inflammatory and oxidative stress markers in mice. By improving muscle function and longevity, the citrate/EDTA-stabilized CNPs could ameliorate amyotrophic lateral sclerosis. Also, they could effectively reduce obesity in mice by scavenging ROS and reducing adipogenesis, triglyceride synthesis, GAPDH enzyme activity, leptin and insulin levels. In CCl4-induced rats, stress signaling pathways due to inflammatory cytokines, liver enzymes, oxidative and endoplasmic reticulum messengers could be attenuated by CNPs. Commercial CNPs showed protective effects on rats with hepatic ischemia reperfusion and peritonitis-induced hepatic/cardiac injuries by decreasing oxidative stress and hepatic/cardiac inflammation. The same CNPs could improve kidney function by diminishing renal superoxide, hyperglycemia and tubular damage in peritonitis-induced acute kidney injury in rats. Radiation-induced lung and testicular tissue damage could be alleviated in mice, with the former showing improvement in pulmonary distress and bronchoconstriction and the latter exhibiting restoration in spermatogenesis rate and spermatid/spermatocyte number. Through enhancement of gastrointestinal motility, the CNPs could alleviate constipation in both young and old rats. They could also protect rat from light-induced retinal damage by slowing down neurodegenerative process and microglial activation.